The influence of shifting the class I cavity position prepared in posterior teeth buccally and lingualy on stress distribution (Finite element analysis study) - Abdulsalm R Al-Zahaw; Kale Masoud M Saeed; Hawzhen Masoud M Saeed (College of Dentistry/ University of Baghdad, 2015)
Background: Rehabilitation of the carious tooth to establish tooth structure integrity required cavity design that show a benign stress distribution. The aim of this study was to investigate the influence of the cavity position on the stress values in the reamining tooth structure restored with amalgam or resin composite. Materials and methods: Seven 2-D models of maxillary first premolar include class I cavity design was prepared, one sound tooth (A) 3 composite (B1, B2, and B3) and 3 amalgam (C1, C2, and C3). In design (BI and C1) the cavity position is in the mid distance between bacc-lingual cusp tip, design (B2 and C2) and (B3 and C3) shifted toward the buccal cusp and the lingual cusp for 0.5 mm respectively. One hundred N vertical load was applied and stress analysis was applied using Ansys v14 software. Results: The maximum Von Mises stress 585.35 MPa in the sound tooth and (899,46, 690.46, and 941.47) in central, buccal, and lingual cavities position filled with a composite restoration respectively. Whereas, the highest stress (1540.37 MPa), (1233.09 MPa) and (1214.34 MPa) appears with a central, buccal and lingual cavities filled with amalgam respectively. Conclusion: Reestablishment of the stress level of maxillary premolars subjected to class I cavity preparations are cavity bacc-lingual position and restorative-system-dependent. Key words: Cavity position, class I, amalgam, composite, stress level.